An Analysis of the Microstructure of the Melting Layer of a Precipitating Stratiform Cloud at the Dissipation Stage - Lei Wei; Hengchi Lei; Wenhao Hu; Minsong Huang; Rong Zhang; Xiaoqing Zhang; Tuanjie Hou; Yuhuan Lü (Atmosphere, 2022)
In this study, we investigated the macro- and microstructures of layered precipitation clouds in spring in Jilin Province, China. The premise of the campaign was to observe cloud particles in the melting layer (ML). The weather was developed under the influence of the Mongolia cyclone, which brought a large range of precipitation to the northeast. Combining the Droplet Measurement Technology (DMT) and Particle Measuring Systems (PMS) data, small particles accounted for the majority of all particles at each level above and below the ML. In our observations, both ice crystals (50–300 μm) and snowflakes (>300 μm) had two peaks between −5 and −2 °C. The high concentration of ice crystals at a temperature of −2.65 °C (4865 m) attained a maximum value of 287 L−1 and snowflakes with 47 L−1, which was similar to the previous studies. The Hallett–Mossop ice multiplication process operated most effectively at the temperature of −5 °C in this study. Even at the cloud dissipation stage, new droplets were still generated between −5 and −6 °C, providing abundant liquid water content (LWC) for the upper cloud. Although irregulars were observed, needles and spheres dominated in the observed cloud region of low LWC (<0.1 g m−3) at temperatures of −6 to −3 °C. These cloud conditions fit into the Hallett–Mossop criteria.